Analisis Pesan Dakwah pada Media Sosial Podcast Login Habib Ja’far dan Onad - Sya'bani, Muhammad Hilmi; Razzaq, Abdur; Hamandia, Muhammad Randicha (Indonesian Journal Publisher, 2024)
Islamic Da'wah is often carried out to spread Islamic knowledge, namely the process of inviting or persuading someone to consciously accept and adhere to a religion in order to awaken and restore a person's innate potential. and live a happy life in this world and the hereafter. The purpose of this research is to determine the da'wah message and communication strategy in the Habib Ja'far and Onad login podcast in the social interaction